Епістолярна спадщина волинезнавця Олександра Цинкаловського - Дяченко, В. (Краєзнавство, 2019)
У розвідці аналізуються епістолярні джерела до життя та діяльності знаного українського
археолога, історика, волинезнавця Олександра Миколайовича Цинкаловського (1898-1983). Показано,
що епістолярій містить біографічні відомості про вченого, розкриває його внутрішній світ, ідейні
та естетичні погляди, індивідуальні риси характеру. Детальний аналіз листування дозволяє пролити
світло на зв'язки Олександра Цинкаловського з оточенням та точніше і адекватніше визначити
його місце у тогочасному науково-історичному процесі. Перспективою дослідження уважаємо
зібрання повного комплексу епістолярних джерел, які стосуються постаті Олександра Цинкаловського. This category refers to information on how the letter was originally sent and how it ultimately arrived.
Regarding the former, there are references in all three corpora to letters being sent by an ‘express’. This term
had multiple meanings, referring not only to the fast delivery of a single letter, or the package in which various
letters were contained, but to the person entrusted with quickly delivering the letter. The research topic is a
study of the epistolary heritage, a little-studied and very important material. This category of sources more obviously
reveals the political, social, economic and cultural condition of the epoch, than other type of historical
material (sources with official narrative, court’s chroniclers historical works); The facts and events of the
private and public life are described in the official and informal letters. The exploration analyses the epistolary
sources of life and work of the famous Ukrainian archaeologist, historian, volynologist Alexander Mykolayovych
Tsinkalovsky (1898-1983). It is shown that the epistolary contains biographical information about the scientist,
reveals his inner world, ideological and aesthetic views, individual character traits. A detailed analysis of the
correspondence makes it possible to shed light on Alexander Tsinkalovsky’s connections with the environment
and to more accurately and more adequately determine his place in the current scientific and historical process.
The prospect of the study is to consider the collection of a complete set of epistolary sources concerning the
figure of Alexander Tsinkalovsky. The article is considered a collection of unread letters A .Tsinkalovsky. Is
outlined history of epistolyaries returning home. Epistolary sources analysed in species characteristics, giving
emphasis to their informative potential.